Random Lasing from a Layer of ZnO Powder Painted on Glass Substrate under Excitation of Nanosecond and Picosecond Laser Pulses - Binh, Nguyen The; Thin, Pham Van; Nga, Pham Thu; Tuan, Nguyen Anh (Communications in Physics, 2012)
The ZnO powder which consists of monodisperse colloidal spheres with average diameter of 100-300 nm was synthesized by hydrolysis of Zinc acetate dehydrate. The random lasing around 380 nm was produced from a layer of the ZnO powder painted on a glass substrate and optically pumped at 355 nm. Our experimental results show that random laser action of a layer of ZnO spherical nanoparticles and the characteristics of these random lasers under excitation of nanosecond and picosecond laser pulses.